Penerapan Model Problem Based Learning Untuk Meningkatkan Kemampuan Berpikir Kritis Matematis Siswa Di SMA Negeri 2 Medan - Yovita Ningtias; Hidayat Hidayat; Dedy Juliandri Panjaitan; Atika Erlina Nasution; Yuki Indayanti (Journal on Education, 2024)
Mathematics is a discipline that focuses on developing thinking skills. Learning mathematics can hone critical thinking skills, which form the foundation for understanding mathematical concepts and effectively solving problems. This Classroom Action Research (PTK) study was conducted to improve students' critical mathematical thinking skills through a PBL approach. Medical School Negeri 2 Medan was the site of the research. A total of 36 students from the 2023/2024 academic year at SMA Negeri 2 Medan's class XI MIPA 9 served as the study subjects. There were two cycles to this research, and each one included the following steps: preparation, action, observation, and reflection. The data was analyzed using quantitative descriptive analysis, and the methods for data gathering included both tests and non-tests. The results showed that the PBL model has improved the critical mathematical thinking skills of students in class XI MIPA 9 at SMA Negeri 2 Medan. In the first cycle, students' critical mathematical thinking skills reached 75.52% with a high qualification, and in the second cycle, they increased to 87.27% with a very high qualification.